No correlation between body mass index and striatal dopamine transporter availability in healthy volunteers using SPECT and [123I]PE2I. (21st May 2013) - Thomsen, G.; Ziebell, M.; Jensen, P. S.; da, S.; Knudsen, G. M.; Pinborg, L. H.
<x xml:space="preserve">Abstract</x> Objective Dopamine plays an important role in both the rewarding and conditioning effects of food. These effects involve mesolimbic, mesocortical, and nigrostriatal pathways. In humans, the most consistent finding has been reduced striatal dopamine D2/3 receptor availability. In striatum, dopamine is inactivated by reuptake via the dopamine transporter (DAT). The aim of the study was to test the hypothesis of lower DAT availability in obese healthy subjects using a selective DAT radiotracer in a sample of subjects with a wide range of BMI values. Design and Methods Thirty‐three healthy subjects with a mean age of 48.4 ± 13.3 (range, 21‐71) years and a mean BMI of 29.6 ± 7.8 kg/m2 (range, 21.0‐49.5) were included in the study. We used [123I]PE2I and SPECT to measure DAT availability. Results Using multiple linear regression analyses with striatal DAT as the dependent variable and BMI, age and gender as predictors was performed. We found no correlation between BMI and striatal DAT availability in striatum (P = 0.99), caudate nucleus (P = 0.61), and putamen (P = 0.30). Furthermore, we found no group difference between obese/severely obese (BMI > 30 kg/m2) and normal weight controls (BMI ≤ 25 kg/m2). Conclusions We did not find any correlation between BMI and DAT availability in healthy volunteers.